Acoustic, mechanical and electric matching in traveling-wave thermoacoustic electric generators - Elbeltagy, Khaled Ali Ali (AUC Knowledge Fountain, 2020)
Traveling-wave thermoacoustic electric generators convert heat energy into acoustic power and then into electrical power. In this work, a toroidal-topology traveling-wave thermoacoustic electric generator is developed. It consists of a traveling-wave thermoacoustic engine, two linear alternators connected in parallel, and sets of variable resistive/capacitive electric loads, in conjunction with accessories and instrumentation required for experimental investigation. The prototype is investigated mostly experimentally, with some theoretical and DeltaEC insights. The main variables are measured, namely the operating frequency of the complete system, the dynamic pressure, the hot side temperatures, the input/output voltages and currents, and the piston stroke. Then, different performance indices are estimated from these measurements, such as the gas parcels oscillating velocity, the different conversion efficiencies, the acoustic and electric output powers. Sustainable operation is achieved over a range of external resistive/capacitive loads at different imposed hot-side temperature, mean gas pressure, and heating rate. Three possible regions of operation are identified: a no-wave region, an operation region, and an over-stroke region. The results identify the two main efficiencies related to the transport of different powers, namely: the thermal-to-acoustic conversion efficiency and the acoustic-to-electric conversion efficiency. The individual factors that control each of them are identified and summarized. The results indicate how the mean gas pressure and the hot-side temperature affect the different key performance indices. For example, the mean gas pressure strongly affects the operating frequency that affects the acoustic matching between the engine and the alternator. Increasing the hot-side temperature improves the thermal-to-acoustic efficiency and extends the operating region into larger regions. The acoustic-to-electric conversion efficiency is controlled solely by the alternator parameter, the resistive/capacitive load combination and the operating frequency. It is observed that the range where the required onset temperature is low corresponds to operation at a large stroke but low current, leading to low electric power output. The study shows that the alternator can produce more current at smaller strokes by increasing the ratio between the Ohmic-to-mechanical-motion loss, which itself depends on the external load and the operating frequency. Two-dimensional contour plots of measured and estimated variables are plotted in the resistive/capacitive load domain in the operating regime, where they quantify the need for acoustic impedance matching for the startup of operation. Theoretical simulations on the performance of the linear alternator at specific strokes and frequencies are examined and compared to the experimental results. DeltaEC simulations are carried out and compared to the experimental measurements. The experimental and DeltaEC results show how different operating variables affect the TAE’s acoustic impedance output, the LA’s acoustic impedance input, and the acoustic impedance matching between them. This thesis identifies and summarizes the different mechanical, acoustic, and electric matching requirements in these devices that are required to either lower the required onset temperature, allow operation in a wide range of electric loads, maximize power output, or overall conversion efficiency. Conflicts between some of these factors are identified, and some practical solutions are suggested. Finally, the main lessons learned during TWTEG’s development are presented.